2012
DOI: 10.4028/www.scientific.net/amr.610-613.2174
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Performance of Modified UASB Process Treating Sewage

Abstract: Added the anaerobic contact oxidation fill area on traditional UASB reactor,the imitation domestic sewage was treated by this modified UASB process on this paper. The COD removal was studied by regulated temperature,hydraulic retention time(HRT) and the influent concentration; The stability of this reactor was studied by regulated pH value of inflow and effluent.The results show that,when regulated the inflow pH value about 7.5,and effluent pH by maintainned about 6.8-7.2,so ensure that the reactor operation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The COD removal efficiency of a UASB reactor also decreases at elevated upflow velocity because higher velocity reduces the contact time between sludge and leachate in addition to smashing of sludge granules, and consequently higher washout of solids [28]. For instance, Nkemka and Murto [28] reported 81% COD removal efficiency at HRT of 12 h in a UASB reactor treating seaweed leachate, while Zhang et al [29] reported 92% COD removal efficiency at HRT of 10 h in a UASB reactor treating sewage. It is also important noticing that the volume of biogas produced towards the end of HRT 48 was insignificant.…”
Section: Biogas Productionmentioning
confidence: 99%
“…The COD removal efficiency of a UASB reactor also decreases at elevated upflow velocity because higher velocity reduces the contact time between sludge and leachate in addition to smashing of sludge granules, and consequently higher washout of solids [28]. For instance, Nkemka and Murto [28] reported 81% COD removal efficiency at HRT of 12 h in a UASB reactor treating seaweed leachate, while Zhang et al [29] reported 92% COD removal efficiency at HRT of 10 h in a UASB reactor treating sewage. It is also important noticing that the volume of biogas produced towards the end of HRT 48 was insignificant.…”
Section: Biogas Productionmentioning
confidence: 99%
“…For higher temperature at pH = 7 the COD removal was higher [ 34 ]. This was because an increase in pH in the range of 6.3–7.8 increase methanogenesis [ 35 , 36 ]. The plot also showed that at pH 7, the % removal of COD was seen to be maximum at a temperature of 24.5 °C beyond this pH the % removal of COD was decreased this is because methanogenesis process is hindered [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…2 It depends on various factors such as acclimatization of seed sludge along with pH, nutrients, organic loading rate, up-flow velocity, HRT, liquid mixing, presence of toxic compounds and reactor design duly effects the development of sludge bed. 29,52 Excellent performance of HUASB reactor is depending on the formation of well settled and greatly active granular sludge, with a high methanogenic activity.…”
Section: Huasb Treatment Initialization and Optimizationmentioning
confidence: 99%